Boundaries of sustainable socio-economic development in the context of the European Green Deal - Adamczyk, Jadwiga (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
The European Green Deal is a response to today’s challenges concerning environmental protection and depletion of natural resources. Among the most important objectives, climate change mitigation and energy transition were identified, and these are linked to socio-economic development. The article presents the theoretical assumptions of sustainable development and the consequences of the implementation of the European Green Deal for social and economic development. Based on the analysis performed, opportunities and threats to the implementation of the European Green Deal are indicated. The publication is financed from the subsidy granted to the Krakow University of Economics within the Support for Conference Activities 2024 programme.